Outcome of carpal tunnel release – Correlation with wrist and wrist–palm anthropomorphic measurements. (February 2015) - Lee, L. H.; Al-Maiyah, M.; Al-Bahrani, R. Z.; Bhargava, A.; Auyeung, J.; Stothard, J.
Wrist and wrist–palm measurements have been associated with the diagnosis of carpal tunnel syndrome. We found no reported study about how this correlation affects the outcome after surgery. We investigated the role of the measurements in predicting outcome after open carpal tunnel release. A total of 131 patients (88 female, 43 male) responded to our postal questionnaire using the Boston Carpal Tunnel assessment (65% response rate) at a minimum of 9 months post-operatively. Symptom and functional scores showed a strong correlation. There was no statistical difference in the outcome between wrist ratio (≥0.7 vs <0.7), wrist–palm ratio (≥0.41 vs <0.41) and gender, but a better functional score was very weakly correlated with a higher wrist ratio. A very large study would be needed to show any statistical correlation between both measurement and outcome.